Chemo-sedimentary facies analysis of fine-grained sediment formations: An example from the Lucaogou Fm in the Jimusaer sag, Junggar Basin, NW China. (December 2019) - Liu, Chang; Liu, Keyu; Wang, Xiaoqi; Zhu, Rukai; Wu, Luya; Xu, Xingyou
Abstract: Fine-grained sedimentary formations occupy about two-thirds of the entire sedimentary sequences in nature. They have recently received great attention owing to the boom of shale oil and gas exploration. Unlike their coarse counterparts, detailed depositional features of fine-grained sedimentary rocks are quite difficult to recognize directly by visual inspection at core or hand specimen scales. A chemo-sedimentary facies analysis (CSFA) procedure has been developed by incorporating high-resolution (down to 30 μm) 2D elemental maps of rock slabs obtained by in situ XRF scanning with high-resolution optical images. The method enables one to unambiguously differentiate rock compositions and fine sedimentary structures and to generate core-scale chemo-sedimentary facies images. The 2D chemo-sedimentary facies map contains major elements with atomic numbers greater than 12, and some trace elements including Ba, V, Cr, Ni, Cu, Zn, Rb, Sr, Y, Zr, Nb, Mo, Th and U at individual pixels. The CSFA procedure was applied to study the Lucaogou Formation, a key shale oil producing interval in the Jimusaer Sag, Junggar Basin, NW China to illustrate three key advantages of CSFA in studying fine-grained sedimentary formations: (1) recognizing invisible sedimentary structures, (2) determining sediment provenances, (3) identifying subtle paleo environmental changes. The Lucaogou Formation has been characterized in unprecedented fine details with sedimentary heterogeneities at centimeter-millimeter scales. Seven chemo-sedimentary facies were delineated in the Lucaogou Formation. Among them, Facies CS-1 was deposited under a relatively deep, fresh to brackish water with strong energy and moist climate; Facies CS-2 was deposited under relatively shallow, brackish water with weak energy arid climate; Facies CS-6 was deposited under relatively shallow, brackish water, arid climate with intermittent hydrodynamic enhancement; Facies CS-7 was deposited in semi-deep, fresh water with strong energy and moist climate. Facies CS-1 and CS-7 have relatively high porosities. The dolomitic fragments in Facies CS-6 was originally deposited in Facies SC-2, but has higher porosities than that of Facies CS-2. Facies CS-6 and Facies CS-7 commonly occur together. The interval with well-developed. Facies CS-1, Facies CS-6 and Facies CS-7 are identified to be the most favorable exploration intervals in the Lucaogou Formation. Highlights: A Chemo-sedimentary facies analysis (CSFA) procedure was proposed to study fine-grained sediment formations. CSFA allows the recognition of invisible sedimentary structures, determining sediment provenance sand identifying subtle paleo environmental changes. Facies CS-1, Facies CS-7 and Facies CS-6 are the most favorable exploration intervals in the Lucaogou Fm.